2017
DOI: 10.1038/s41467-017-02248-y
|View full text |Cite
|
Sign up to set email alerts
|

Mineral surface chemistry control for origin of prebiotic peptides

Abstract: Some seventy years ago, John Desmond Bernal proposed a role for clays in the origin of life. While much research has since been dedicated to the study of silicate clays, layered double hydroxides, believed to be common on the early Earth, have received only limited attention. Here we examine the role that layered hydroxides could have played in prebiotic peptide formation. We demonstrate how these minerals can concentrate, align and act as adsorption templates for amino acids, and during wetting—drying cycles,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
99
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(102 citation statements)
references
References 40 publications
3
99
0
Order By: Relevance
“…The activity of the water generated in these proto-biosynthetic reactions may have been kept low in the hydrous innards of green rust and mackinawite through exosmosis to the salty surrounds. [93,186] The AHV theory as it stands, focuses on how the hydrous interlayers or channels in green rust, and to a lesser degree in mackinawite, likely mediated the imposed proton gradient and, through the bifurcation of electron pairs, effectively stepped up the redox gradients to the effect of driving an organic takeover. [4] We are conscious that the relative contributions of green rust, mackinawite and associated minerals, and how they may have cooperated in Leduc's 'synthetic biology', has been left unresolved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activity of the water generated in these proto-biosynthetic reactions may have been kept low in the hydrous innards of green rust and mackinawite through exosmosis to the salty surrounds. [93,186] The AHV theory as it stands, focuses on how the hydrous interlayers or channels in green rust, and to a lesser degree in mackinawite, likely mediated the imposed proton gradient and, through the bifurcation of electron pairs, effectively stepped up the redox gradients to the effect of driving an organic takeover. [4] We are conscious that the relative contributions of green rust, mackinawite and associated minerals, and how they may have cooperated in Leduc's 'synthetic biology', has been left unresolved.…”
Section: Discussionmentioning
confidence: 99%
“…Erastova and her collaborators -noting how mineral surfaces "may have very high enthalpies of rehydration" and thereby provide "a driving force for condensation reactions" -have suggested, through molecular dynamics simulations, how layered hydroxides can concentrate, align and act as adsorption templates for amino acids, and promote peptide bond formation. [186] Moreover, following Amend and Shock, Kitadai has found that -in regard to the thermodynamics of amino acid synthesis and polymerization -"hot, alkaline hydrothermal systems beneath cool, slightly acidic Hadean ocean are an energetically excellent setting among possible vent-ocean combinations". [187,188] It might be argued that the water generated in these protobiochemical processes would tend to lyse any product.…”
Section: Green Rust -The First Organizing Nanoengine Of Life?mentioning
confidence: 99%
“…Also omitted are the interlayer water molecules that act as a proton wire within and along the green rust nanocrysts . Four further water molecules are produced per molecule of ammonia and more water still is produced through other reductions and condensations, leading to a low osmolarity in the interlayers compared to the ocean and hydrothermal fluid on either side of the membrane . Influenced by oscillating temperature, this non‐structural (waste) water is “sucked” out of the interlayers through exosmosis into these salty solutions, thus maintaining low water activity within the galleries .…”
Section: What Does All This Have To Do With the Emergence Of Life?mentioning
confidence: 99%
“…Four further water molecules are produced per molecule of ammonia and more water still is produced through other reductions and condensations, leading to a low osmolarity in the interlayers compared to the ocean and hydrothermal fluid on either side of the membrane . Influenced by oscillating temperature, this non‐structural (waste) water is “sucked” out of the interlayers through exosmosis into these salty solutions, thus maintaining low water activity within the galleries . In these same galleries the ammonia can go on to effect the amination of amino acids which may then polymerize to heterochiral peptides.…”
Section: What Does All This Have To Do With the Emergence Of Life?mentioning
confidence: 99%
“…Previous studies indicate that surfaces might have played a role in catalysis and synthesis of compounds relevant to prebiotic chemistry, e.g. enhanced polymerization of aminoacids on mineral surfaces 11 , or the synthesis of prebiotic peptides 12 and RNA 13 . Our work shows that the surface-assisted subcompartmentalization of protocells is a feasible recurring process and, due to the minimal requirements, could have potentially occurred under early Earth conditions.…”
mentioning
confidence: 99%